Odpowiedź :
a) obw = 2πr
26π = 2πr /÷2
13 = r
b) 15 = 2πr /÷ 2π
7,5/π = r
c) P = πr²
1,21 = πr² /π
1,21/π = r²
1,1/√π =r
d) P = πr²
4 = πr² /÷π
4/π = r²
2/√π = r
26π = 2πr /÷2
13 = r
b) 15 = 2πr /÷ 2π
7,5/π = r
c) P = πr²
1,21 = πr² /π
1,21/π = r²
1,1/√π =r
d) P = πr²
4 = πr² /÷π
4/π = r²
2/√π = r
obw = 26pi
26pi = 2pir
26=2r |:2
r=13
l=15pi
15pi = 2pir
15 = 2r |:2
r=7,5
p= 1,21
p= pir^
1,21 = pir^ |:pi
1,21/pi = r^
r= pierwiastek z 1,21/pi
p=4pi
4pi = pir^
4=r^
r=2
26pi = 2pir
26=2r |:2
r=13
l=15pi
15pi = 2pir
15 = 2r |:2
r=7,5
p= 1,21
p= pir^
1,21 = pir^ |:pi
1,21/pi = r^
r= pierwiastek z 1,21/pi
p=4pi
4pi = pir^
4=r^
r=2